Some observations on the sand dunes and vegetation of Bikaner district in western Rajasthan - Saxena, S K; Singh, S (Annals of Arid Zone, 2016)
The morphology and vegetation of five types of dunes namely parabolic, longitudinal, transverse, barchan and shrubcoppice of Bikaner district have been discussed. The results of the morphological studies of the dunes have revealed that the dunes of the first three types belong to an old dune system. Within the systems, the parabolic dunes occupy larger areas, are better stabilized and contain higher percentages of calcium carbonate and fine sand particles (70 to 120 micron dia.) than all the other types of dunes. Two vegetation types have been recognized on dunes of the old system, viz. " Psammophytic Scrub Desert" and "Mixed Xeromorphic" Thorn Forest" Calligonum polygonoides - Panicum turgidum is the most common plant community of Psammophytic Scrub Desert which occurs on all tree types of dunes of the old system. The plant density and number of three are more on parabolic dunes than other dunes which also indicate better stabilisation of the former type of dunes. The higher density of Calligonum polygonoides on the longitudinal dunes indicates that these dunes have been reactivated by aeolian activities and that fresh sands are piled on them. Presence of Prosopis cineraria on the lower slopes of longitudinal dune and that of Haloxylon salieornicum on the lower slopes of the transverse dunes have been observed. The therophytic species found on the three types of stabilized dunes are more or less similar, except for their densities. However, only a limited variety of specks occur in the western sector. It is inferred from these studies that the dunes of the old system do not need any plantation to ensure their stability but must be protected from biotic interference. The dunes of the new system are active and must be stabilized through suitable dune stabilistion techniques involving the use of psammophytic indigenous species which are well adapted to the existing environmental conditions of the sand dunes.